Catholic Belfast and Nationalist Ireland in the era of Joe Devlin, 1871-1934 - Hepburn, A. C. (Anthony C.) (Oxford University Press, 2008)
This text offers a re-interpretation of Irish political history in the partition era from the perspective of the losers. It is a general text covering 50 years of Irish political history, as well as a case study of Catholic Belfast and a biography of Joe Devlin.